Elongator function in tRNA wobble uridine modification is conserved between yeast and plants - Mehlgarten, Constance (Blackwell Publishing Ltd, 2010)
Based on studies in yeast and mammalian cells the Elongator complex has been implicated in functions as diverse as histone acetylation, polarized protein trafficking and tRNA modification. Here we show that Arabidopsis mutants lacking the Elongator subunit AtELP3/ELO3 have a defect in tRNA wobble uridine modification. Moreover, we demonstrate that yeast elp3 and elp1 mutants expressing the respective Arabidopsis Elongator homologues AtELP3/ELO3 and AtELP1/ELO2 assemble integer Elongator complexes indicating a high degree of structural conservation. Surprisingly, in vivo complementation studies based on Elongator-dependent tRNA nonsense suppression and zymocin tRNase toxin assays indicated that while AtELP1 rescued defects of a yeast elp1 mutant, the most conserved Elongator gene AtELP3, failed to complement an elp3 mutant. This lack of complementation is due to incompatibility with yeast ELP1 as coexpression of both plant genes in an elp1 elp3 yeast mutant restored Elongator's tRNA modification function in vivo. Similarly, AtELP1, not ScELP1 also supported partial complementation by yeast–plant Elp3 hybrids suggesting that AtElp1 has less stringent sequence requirements for Elp3 than ScElp1. We conclude that yeast and plant Elongator share tRNA modification roles and propose that this function might be conserved in Elongator from all eukaryotic kingdoms of life.